Feasibility of Android-Based Physics Learning Media on Dynamic Electricity - Sugiarto, Gerry; Fathurohman, Apit; Yusup, Muhamad (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
The purpose of this research is to determine: (1) validation of android-based physics learning media on dynamic electricity material for Class XII SMA students (2) the effectiveness of Android-based Physics Learning Media on dynamic electricity material for XII Class SMA students. The research method used is development research which refers to the development of Allesi and Trollip which includes: the planning stage, the design stage, and the development stage. This Learning Media was validated by 2 content validators, 2 media validators, and 5 students to determine its eligibility based on the feasibility aspects of content, language, presentation, and graphics. After being validated and fulfilling the eligibility criteria. The results of the development of android-based learning media are: (1) Learning media is feasible and practical to use (2) Learning media is in accordance with student learning styles and student learning independence